Continuous production of Jatropha curcas L. biodiesel using oscillatory flow biodiesel reactor - Muhammad Syam, Azhari (2011)
Jatropha curcas L. biodiesel (methyl esters) was successfully synthesized from esterified Jatropha curcas L. oil (JCO) via transesterification process using an oscillatory flow reactor (OFR). Alkaline catalysts were used in this process, and the effects of operating variables such as molar ratio, reaction temperature, reaction time, and the percentage of catalyst loading were investigated. The reactions were carried out under atmospheric pressure. The reaction temperatures were varied between 50 to 70 °C. The effects of two alkaline catalysts namely potassium hydroxide (KOH) and sodium hydroxide (NaOH) and molar ratio of methanol to JCO on reaction yield were investigated. The optimum conditions for batch mode in the presence of KOH catalyst were as follows: reaction temperature at 65 °C, reaction time at 30 min, molar ratio at 6:1, and catalyst amount at 1.0% w/w. The maximum reaction conversion attainable using batch process was at 99%. The design of the OFR was carried out based on the principle of maintaining geometric and dynamic similarity of various dimensionless groups. This was followed by the application of other empirical design correlations specific to the oscillatory flow system. Using the designed OFR, the transesterification of JCO was accomplished in the presence of KOH and NaOH catalysts at the optimal conditions of 60 °C, molar ratio at 6:1, reaction time of 15 min and oscillation frequency of 6 Hz. The maximum conversion obtained was 99.7% and 90% for KOH and NaOH catalysts, respectively. The OFR performed better than the batch reactor due to its advantages in achieving a perfect superimposed mixing of fluids by forcing the upstream into the baffles area, thus a shorter time was required to complete the reaction. One of the major problems associated with the use of biodiesel, especially prepared from palm oil, is its poor low temperature flow property. Jatropha curcas L. biodiesel, however, has a good low temperature property, comparable to conventional biodiesel feedstock such as rapeseed oil. This is due to the fatty acid composition of JCO which is rich in oleic and linoleic acids. From the results of analysis done on the Jatropha curcas L. biodiesel, the pour point and the cloud point of the biodiesel were -10 °C and -6 °C, respectively. This indicates that the oil is suitable for winter grade biodiesel. Other quality tests also showed that the Jatropha curcas L. biodiesel meets the majority of the quality standards of both EN 14214 and ASTM D6751. In addition, the kinetics study on transesterification of JCO with methanol had established that the kinetics were governed by two stepwise and irreversible elementary reactions and conformed to follow the first order reaction model. The rate constants for the formation of intermediate diglycerides and the final product Jatropha curcas L. methyl esters (biodiesel) were determined at various temperatures. The values of kTG ranged from 0.12 to 0.17 and the values of kDG ranged from 0.13 and 0.20. The activation energies for stepwise reaction in transesterification of JCO with methanol ranged from 6.55 to 11.18 kcal/mol. Simulation of three stepwise reversible reactions in the transesterification process was also carried out using MATLAB®. The results from the simulation indicated that the reaction rate constants were affected significantly by reaction temperature. At higher temperature, the rate constant for forward reactions (kf) increased markedly with temperature while for the reverse reactions, the rate constant (kr) was less affected by the temperature. This is evidenced by the smaller kr values compared to kf values. Based on the statistical analysis, the results showed good correlations with the experimental data based on SSE, RMSE and Chi-square (χ2) values. The proposed model for kinetics of reversible transesterification process fitted well with the experimental data.